FICTITIOUS HUMAN CAPITAL: CONCEPTUAL APPROACHES AND FEATURES OF EVALUATION - O. Brintseva (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The basic methods of human capital valuation are studied in the article (method of representative estimates; valuation based on previous spending; valuation based on the impact of the use of human capital; market method). The valuation of national human capital is carried out. Considering to the fiktyvization processes, the significant adverse effects of it to the national economy and social and labor sphere, evaluation of fictitious human capital are conducted. Results of the conducted research demonstrate that from 2,4% to 8,2% of investments in human capital are directed to formation of the fictitious human capital in education, health care and the social and labor sphere. The ways of improving the efficiency of investment in human capital, to overcome the negative impact of fiktyvization trends are determined.